2014
DOI: 10.1063/1.4891346
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear space charge dynamics in mixed ionic-electronic conductors: Resistive switching and ferroelectric-like hysteresis of electromechanical response

Abstract: Articles you may be interested in Frequency dependent dynamical electromechanical response of mixed ionic-electronic conductorsWe performed self-consistent modelling of nonlinear electrotransport and electromechanical response of thin films of mixed ionic-electronic conductors (MIEC) allowing for steric effects of mobile charged defects (ions, protons, or vacancies), electron degeneration, and Vegard stresses. We establish correlations between the features of the nonlinear space-charge dynamics, currentvoltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
(135 reference statements)
0
17
0
Order By: Relevance
“…Following this, Noheda group has recently shown that ferroelectric phase of HfO 2 has polarization in (111) orientation, this providing the possible explanation for complex polarization dynamics observed in (100) films [19]. However, in parallel to this intrinsic model for the ferroelectricity, a number of authors offer strong evidence on the role of vacancies on materials behavior, including the role of preparation and annealing conditions, possible reactions at electrodes, and general proximity of ferroelectric and electroresistive switching [20,21,22,23]. For example, Polakowski and Muller [17] used conventional wake-up technology and did not observed ferroelectricity in the 20-nm thick undoped HfO 2 film, while the ferroelectric (FE) phase was observed for undoped HfO 2 film of thickness h ~ 35 nm by Nishimura et al [16], who annealed the films in N 2 atmosphere.…”
Section: A Observation Of Ferroelectricity and Ferromagnetism Of Hfomentioning
confidence: 99%
“…Following this, Noheda group has recently shown that ferroelectric phase of HfO 2 has polarization in (111) orientation, this providing the possible explanation for complex polarization dynamics observed in (100) films [19]. However, in parallel to this intrinsic model for the ferroelectricity, a number of authors offer strong evidence on the role of vacancies on materials behavior, including the role of preparation and annealing conditions, possible reactions at electrodes, and general proximity of ferroelectric and electroresistive switching [20,21,22,23]. For example, Polakowski and Muller [17] used conventional wake-up technology and did not observed ferroelectricity in the 20-nm thick undoped HfO 2 film, while the ferroelectric (FE) phase was observed for undoped HfO 2 film of thickness h ~ 35 nm by Nishimura et al [16], who annealed the films in N 2 atmosphere.…”
Section: A Observation Of Ferroelectricity and Ferromagnetism Of Hfomentioning
confidence: 99%
“…Mixed ionic-electronic conductors, such as solids with rechargeable ions or vacancies, which also can be mobile, free electrons and/or holes, can display a reversible dynamics of the space charge layers that leads to a pronounced resistive switching between meta-stable states with high and low resistance [93][94][95][96][97][98] and unique dynamic properties (including hysteretic) electromechanical response. [99][100][101][102][103][104][105][106] Though ferroelectrics with mixed type conductivity (FeMIECs) are promising candidates for the nonvolatile and memristive [107][108][109] memory devices, the physical principles of the charge transfer phenomena at their surfaces and interfaces are far from clear. [102] Space charge dynamics in ferroelectric thin films were studied theoretically primarily in the framework of linear drift-diffusion Poisson-Planck-Nernst theory and diluted species approximation.…”
Section: Ii3 Coupling Between Physics and Electrochemical Behaviorsmentioning
confidence: 99%
“…[99][100][101][102][103][104][105][106] Though ferroelectrics with mixed type conductivity (FeMIECs) are promising candidates for the nonvolatile and memristive [107][108][109] memory devices, the physical principles of the charge transfer phenomena at their surfaces and interfaces are far from clear. [102] Space charge dynamics in ferroelectric thin films were studied theoretically primarily in the framework of linear drift-diffusion Poisson-Planck-Nernst theory and diluted species approximation. [105,107,110,111] However one can expect a strong correlation between the electrochemical and electromechanical response in FeMIECs, because the spatial gradient of mobile species (ions, vacancies and electrons) concentration near the surface caused by electromigration (electric field-driven for charged species) and diffusion (concentration gradientdriven for both charged and neutral species) mechanisms can change the lattice molar volume.…”
Section: Ii3 Coupling Between Physics and Electrochemical Behaviorsmentioning
confidence: 99%
“…ESM was extended to regimes with both diffusive and migration transport for open and blocking 259 electrodes, giving rise to more complex time dispersion of responses. 289,328 The important aspect of pure Vegard mechanisms is that it does not predict the formation of remnant states with opposite electromechanical responses and hysteresis loops beyond kinetic ones. Combined with the explicit assumption of fast surface reactions, these mechanisms can be relegated to purely electrochemical systems under rapid electrochemical control, e.g.…”
Section: Ferroelectric Switchingmentioning
confidence: 99%